Challenges to Journalists’ Safety in Covering Boko Haram Insurgency in the North-East, Nigeria - Abdulkadir, Ibrahim (Budapest International Research and Critics University, 2025)
This study examined the challenges to journalists’ safety in covering the Boko Haram insurgency in North East, Nigeria. The research sought to assess the nature of safety challenges journalists face, the level of safety they have, to identify the safety routine measures journalists adopted before fieldwork, and find out whether media organisations provide safety measures to their reporters. The Protection Motivation was reviewed and used as framework for the study. To achieve these objectives, a qualitative research approach was used as a means of getting valuable data. Focus Group Discussion (FGD) was selected as the methods for gathering relevant information. A sample size of 41 participants was selected for the FGD using purposive sampling technique. Thematic analysis method was used in analysing the data generated, which was used in answering the research questions. The study found out that journalists who cover the Boko Haram insurgency in the North East adopt various local and international best safety practices laid down for journalists covering dangerous assignments. The data also revealed that the safety routine measures adopted by journalists before fieldwork reduced risk and improved safety. The findings further revealed that media organizations do not provide safety measures for journalists and that the safety of journalists covering the Boko Haram insurgency in the North East is solely their responsibility. The research concludes that the issue of safety and protection of journalists in Nigeria must be given due consideration by the government and media stakeholders. The way and manner journalists lose their lives in the process of discharging their duty is alarming. The study recommends that the safety and protection of journalists should be made part of journalists’ employment contracts, and there should be a national protection and safety protocol curriculum and training for journalists.